2015
DOI: 10.1163/15685403-00003411
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale oceanic circulation and larval recruitment of the spiny lobster Panulirus argus (Latreille, 1804)

Abstract: The most important populations of the spiny lobster (Panulirus argus (Latreille, 1804)) in the Atlantic are found in the Caribbean and along the Brazilian coast. Field studies covering the waters off the Cuban archipelago and Brazil have improved our understanding of the importance of oceanic circulation to larval recruitment. South of Cuba, puerulus settlement is intensive in October and November when the coastal reefs (83°W) are impacted by a cyclone-anticyclone pair, suggesting this area is the main source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 42 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…We found that puerulus settlement in the Northern zone of South Australia peaked in some years, interspersed by periods of lower settlement, which suggests that settlement was driven by environmental factors that cause high variation in settlement, such as ocean currents (Cruz et al, 2015;Griffin et al, 2001) and wind strength (de Lestang et al, 2015;Groeneveld et al, 2010;Linnane, James, et al, 2010).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…We found that puerulus settlement in the Northern zone of South Australia peaked in some years, interspersed by periods of lower settlement, which suggests that settlement was driven by environmental factors that cause high variation in settlement, such as ocean currents (Cruz et al, 2015;Griffin et al, 2001) and wind strength (de Lestang et al, 2015;Groeneveld et al, 2010;Linnane, James, et al, 2010).…”
Section: Discussionmentioning
confidence: 78%
“…We found that puerulus settlement in the Northern zone of South Australia peaked in some years, interspersed by periods of lower settlement, which suggests that settlement was driven by environmental factors that cause high variation in settlement, such as ocean currents (Cruz et al., 2015; Griffin et al., 2001) and wind strength (de Lestang et al., 2015; Groeneveld et al., 2010; Linnane, James, et al., 2010). To ensure fishery sustainability, harvest strategies should conserve recruitment pulses within spiny lobster fisheries, particularly considering the extended larval phase of the species (Linnane et al., 2013; Plagányi, McGarvey, et al., 2018).…”
Section: Discussionmentioning
confidence: 80%
“…However, the NBC also curves back to the east (reflects) between July and December around 6–8° N (as shown in Fig. 1 ) shedding eddies and rings that may flow eastward, possibly helping to interconnect the reef environments 70 , 71 . In this scenario, the SAC hard substrates effectively constitute stepping-stones between ARS and ERS, providing adequate substrates for at least some species, aiding larval dispersion, ontogenetic migration, and small-scale movements of adult animals, which are key processes connecting Western Atlantic reef systems 45 , 72 , 73 .…”
Section: Discussionmentioning
confidence: 99%
“…The MHE of Ceará are home to juveniles of many species of fish, such as the dog snapper (Lutjanus jocu) and the black grouper (Mycteroperca bonaci) (Bezerra et al, 2017;Godinho & Lotufo, 2010), indicating that such ecosystems have an important role in the reproductive cycle of these organisms (Eggertsen et al, 2017). Similarly, the life cycle of the red lobster (Panulirus meripurpuratus, former P. argus) and green lobster (P. laevicauda), which are among the main fishing targets in the state, depends heavily on the coastal MHE, because their life stage after larval settlement takes place in these environments (Cruz et al, 2015). Previous studies have also proposed the existence of important exchanges of matter and energy (including species) between shallow-and deep-water MHE Tavares & Carneiro, 2019).…”
Section: Economic Importancementioning
confidence: 99%